El uso de Internet en América Latina (2011)
This paper explores the development of Internet use in Latin America. The analysis explores the macro- and microsocial expectations and actualities of Internet use in Latin America. While much is assumed about Internet penetration in the region, this paper lays out actual penetration rates, and attempts to understand what has fostered Internet growth in the region. Various levels of economic, technological, and governmental development encourage the expansion of Internet penetration in the region. By looking at micro-level Internet consumption, this research employs Latin American Public Opinion Project survey data taken from multiple years and offers an initial analysis of the determinants of Internet use. Compared to other forms of news media consumption, Internet users are younger and more skeptical of domestic news media.